Effects of Isotretinoin treatment on human body - review - Słomczyński, Adam; Zatyka, Piotr; Pawłowska, Agata; Rabenda, Michal; Janik, Piotr; Osuch, Dobromiła; Opala, Dominika (Quality in Sport, 2024)
Introduction: Isotretinoin (13-cis-Retinoic Acid) is a part of the retinoid group, and is used in dermatology for the treatment of acne, due to its demonstrated inhibitory effect on sebaceous gland activity and proliferation. Isotretinoin is a highly lipophilic drug, for this reason taking it with food, doubles the bioavailability of the substance, during systemic treatment. Isotretinoin as a drug has been used effectively for more than 40 years in the treatment of acne, although its exact mechanism of action is not known. Objective: The objective of this study is to gather and analyze literature regarding the adverse effects of isotretinoin therapy on mental health and the digestive, cardiovascular, immune, urinary, and reproductive systems. Materials and Methods: A literature review was conducted using the PubMed database with the following search terms : retinoids, isotretinoin, acne, 13-cis-retinoic acid. Current Knowledge: Isotretinoin therapy has a vast spectrum of side effects affecting various systems of the human body. During the use of isotretinoin, special caution should be taken in patients with depression, lipid disorders, and abnormal liver function. In addition, in patients of childbearing age, make sure to use contraception one month before, during and one month after the end of isotretinoin therapy due to its teratogenicity. Conclusion: Isotretinoin is still the most effective drug in the systemic treatment of severe forms of acne, nevertheless its potential side effects should be kept in mind. Regular monitoring of patients should be a mainstay during isotretinoin therapy, especially with regard to lipid profile and liver parameters.